Harmonization of Multi-Religious Family Culture in the Religious Moderation Village of Malang City - Hawa’ Hidayatul Hikmiyah; Muhil Mubarok; A. Fikri Amiruddin Ihsani (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
The Ministry of Religion of Malang City in September 2023 launched a religious moderation village. From this village, there are families who have multiple religions, whether from the father, mother, or child. In this case, the head of the Ministry of Religion hopes that there will be an emphasis on the urgency of togetherness and moderation in religion to realize harmony in the Indonesian state, because religious diversity in Indonesia has great potential that must be protected and fostered, especially through a religious moderation program that must be pursued from the smallest sector of the State, namely a multi-religious family. In this study, field research was used to obtain objective, actual, and strong data. The data source was taken directly from the research location, which was done by visiting the informants through interviews. The researcher conducted interviews with multi-religious families in the religious moderation village in Malang City. Multifaith families often face challenges both within and outside the family. The most common challenge is social pressure, meaning that in societies where interfaith marriages and families are accepted or extended families are accepted, although not common, family members may put pressure on spouses and children to choose a religion.